Actininopathy: A new muscular dystrophy caused by ACTN2 dominant mutations. Issue 6 (3rd April 2019) - Savarese, Marco; Palmio, Johanna; Poza, Juan José; Weinberg, Jan; Olive, Montse; Cobo, Ana Maria; Vihola, Anna; Jonson, Per Harald; Sarparanta, Jaakko; García‐Bragado, Federico; Urtizberea, Jon Andoni; Hackman, Peter; et al.
Abstract : Objective: To clinically and pathologically characterize a cohort of patients presenting with a novel form of distal myopathy and to identify the genetic cause of this new muscular dystrophy. Methods: We studied 4 families (3 from Spain and 1 from Sweden) suffering from an autosomal dominant distal myopathy. Affected members showed adult onset asymmetric distal muscle weakness with initial involvement of ankle dorsiflexion later progressing also to proximal limb muscles. Results: In all 3 Spanish families, we identified a unique missense variant in the ACTN2 gene cosegregating with the disease. The affected members of the Swedish family carry a different ACTN2 missense variant. Interpretation: ACTN2 encodes for alpha actinin2, which is highly expressed in the sarcomeric Z‐disk with a major structural and functional role. Actininopathy is thus a new genetically determined distal myopathy. ANN NEUROL 2019;85:899–906.